2022
DOI: 10.2147/prbm.s349074
|View full text |Cite
|
Sign up to set email alerts
|

The Hierarchical Relationship Between the Relational-Self and the Collective-Self During Attention Processing

Abstract: Background Under the Chinese collectivist cultural system, people emphasize social connections with close others and members of in-groups. Collectivism can be divided into the following two forms: relational collectivism (privileges relational self [RS]) and group collectivism (emphasizes collective self [CS]). Previous researchers have found a hierarchy between the RS and CS, resulting in different degrees of recognition advantages. However, the hierarchy between the RS and CS is unclear and may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, one may also consider how they share similarities and connection through relationships (collectivist perspective; Cohen & Gunz, 2002;Ownsworth, 2014). Empirical studies have shown that Chinese people placed more emphasis on their relational and collective selves, on their identity as a member of their nation, and also prefer to maintain and enhance their collective self-esteem (Ma et al, 2016;Zheng et al, 2017;Zheng et al, 2018). For example, student YJB was very proud to say, "I think China is a country that has done a great job in many ways, ... (I want to) maintain this high sense of identity with my country.…”
Section: Resultsmentioning
confidence: 99%
“…However, one may also consider how they share similarities and connection through relationships (collectivist perspective; Cohen & Gunz, 2002;Ownsworth, 2014). Empirical studies have shown that Chinese people placed more emphasis on their relational and collective selves, on their identity as a member of their nation, and also prefer to maintain and enhance their collective self-esteem (Ma et al, 2016;Zheng et al, 2017;Zheng et al, 2018). For example, student YJB was very proud to say, "I think China is a country that has done a great job in many ways, ... (I want to) maintain this high sense of identity with my country.…”
Section: Resultsmentioning
confidence: 99%
“…Inconsistent with our results, a study found a primacy of the collective self vs. the IS and relational self when using self-relevant information and asked participants to make subjective judgements on these stimuli ( Wang et al, 2017 ). Researchers also found that at the early stage, especially during implicit processing, the sense of belonging to the group and self-identity as a group member is prominent ( Zheng et al, 2018a ). The difference in results may be due to our perception matching paradigm that excluded the influence of self-related information.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no difference between the relational self and collective self. Another study using implicit association tasks found that Chinese people render the collective self as primary compared to the relational self ( Zheng et al, 2017 , 2018a ). Using a priming paradigm, Wang et al (2017) found that during the early (P2) stage, people render their IS as their primary self; their relational self as secondary; and their collective self as tertiary.…”
Section: Introductionmentioning
confidence: 99%
“…According to self‐categorization theory, the better fit the stimuli is, the more likely a group is to be viewed as similar (Oakes, Turner & Haslam, 1991). According to the tripartite model of self‐construal theory (Sedikides & Brewer, 2002), individual self, collective self, and relational self have different dominance depending on culture and context (Zheng, Xiao, Chen, Hu & Zhou, 2018). Since live groups are usually relational groups (Brewer & Chen, 2007), interdependent self‐construal individuals fit the live group better than the minimal group.…”
Section: Discussionmentioning
confidence: 99%